A low-kiloelectronvolt focused ion beam strategy for processing low-thermal-conductance materials with nanoampere currents - Wolff, Annalena; Klingner, Nico; Thompson, William; Zhou, Yinghong; Lin, Jinying; Xiao, Yin (Beilstein Journal of Nanotechnology, 2024)
Ion beam-induced heat damage in thermally low conductive specimens such as biological samples is gaining increased interest within the scientific community. This is partly due to the increased use of FIB-SEMs in biology as well as the development of complex materials, such as polymers, which need to be analyzed. The work presented here looks at the physics behind the ion beam–sample interactions and the effect of the incident ion energy (set by the acceleration voltage) on inducing increases in sample temperature and potential heat damage in thermally low conductive materials such as polymers and biological samples. The ion beam-induced heat for different ion beam currents at low acceleration voltages is calculated using Fourier’s law of heat transfer, finite element simulations, and numerical modelling results and compared to experiments. The results indicate that with lower accelerator voltages, higher ion beam currents in the nanoampere range can be used to pattern or image soft material and non-resin-embedded biological samples with increased milling speed but reduced heat damage.
Keywords: biological sample; COMSOL; focused ion beam; forward time–centered space (FTCS); heat damage; SRIM